Psychological Contracts of Multiple Jobholders: A Multilevel Analysis. (May 2018) - Raeder, Sabine
Organizational research has paid little attention to multiple jobholders. This study investigated the psychological contracts of multiple jobholders in relation to each employment contract and the nonstandard work arrangement of multiple jobholding. The sample consisted of 141 multiple jobholders with two or more jobs and either employed or self-employed status. The results of the multilevel analyses indicated that, with one exception, psychological contract obligations vary more between employment relationships than between individuals. Multiple jobholders' psychological contracts are only partly related to the terms of their employment contracts and their nonstandard work arrangement. This study connects mainly economic knowledge on multiple jobholders to the organizational variable psychological contracts. Investigating the psychological contracts within and between multiple jobholders helps researchers better understand psychological contracts and how they are related to the job. Typical patterns of multiple jobholders' employment situation and psychological contracts can thus be identified.